Grab the Mic @ UiTMCPP / Marni Jamil - Jamil, Marni (Academy of Language Studies, 2023)
an event that aimed to promote a culture of idea sharing was successfully organised by the Chemical Engineering Student Society (ChESS) of Universiti Teknologi MARA UiTM, Cawangan Pulau Pinang (UiTMCPP) on the 10th November 2022. Ms. Marni Jamil, a lecturer from the Academy of Language Studies, UiTMCPP who is also a public speaking instructor delivered an uplifting speech titled ‘Everything Under the Sun’, which focused on the development of tertiary students’ knowledge and skills. The TED-style talk held at the SUDI Cafeteria, UiTMCPP, garnered the interest of members of the university community who were aptly present during lunchtime. It brought forth ideas that encouraged people in academia to reflect on the significance of upskilling, strategic collaboration and visibility. The value of teamwork was highlighted through the emphasis on linkages creation by inspiring them to accomplish greater heights together and fostering a sense of camaraderie. Moreover, moving forward in the digital arena, exhibiting and expressing one's work via digital platforms is without a doubt an essence of the future. Overall, the event has amplified a sense of hope and empowerment to unleash the true potential of individuals.